A pressure sensor based on the orientational dependence of plasmonic properties of gold nanorods. Issue 34 (10th August 2015) - Fu, Lishun; Liu, Yiding; Wang, Wenshou; Wang, Mingsheng; Bai, Yaocai; Chronister, Eric L.; Zhen, Liang; Yin, Yadong
Abstract : A novel pressure sensor has been developed by taking advantage of the orientational dependence of localized surface plasmon resonance of gold nanorods embedded in a polymer matrix. Abstract : A novel pressure sensor has been developed by taking advantage of the orientational dependence of localized surface plasmon resonance of gold nanorods embedded in a polymer matrix. This stress-responsive material can be used to record the distribution and magnitude of pressure between two contacting surfaces by outputting optical response.